Role of central alpha-1 adrenoceptors in canine narcolepsy. - Mignot, E (1988)
The role of central alpha-1 adrenergic receptors in cataplexy was investigated in genetically narcoleptic Doberman pinschers. Treatment of narcoleptic dogs with 25-600 micrograms/kg prazosin, a selective alpha-1 adrenergic receptor blocker, exacerbated cataplexy, whereas treatment with the alpha-1 agonist, methoxamine, ameliorated it. Subsequent studies showed that the beneficial effects of classical treatments of human narcolepsy (amphetamines and tricyclic antidepressants) are antagonized by prazosin, suggesting that these drugs are active through an indirect alpha-1 stimulation (via an increase of norepinephrine in the synaptic cleft). Other studies confirmed that the observed effects were not due to peripheral alpha-1 cardiovascular involvement. Atropine, a central anticholinergic agent, but not methylatropine, a peripheral one, completely suppressed the prazosin effect, which suggests that adrenergic and cholinergic systems act sequentially and not independently to generate cataplexy. Little is known about the physiological role of central alpha-1 adrenoceptors. This series of experiments implicates these receptors in narcolepsy-cataplexy.